Analisis Komoditas Biofarmaka Unggulan di Kabupaten Karanganyar - Putri, Novel Handhika; Dewati, Rosita; Arianti, Yoesti Silvana (Journal of Agribusiness, Social and Economic, 2021)
Local governments are given autonomy in order to explore and utilize the potential of the region, including the use of land resources for the development of the agricultural sector. Karanganyar Regency uses land for biopharma commodities. This research aims to identify leading biopharmaceutical commodities and establish priority areas for the development of leading commodities in Karanganyar Regency. The analysis model used is descriptive analysis, location quotient analysis, and shift share analysis. The results showed that ginger and turmeric commodities are excellent commodities and have high potential to be developed. The development of ginger commodity is prioritized to Kerjo and Jenawi sub-districts while turmeric commodities to Jatiyoso and Jumapolo subdistricts